Biomechanical analysis of backstroke to breaststroke turns in age-group swimmers: An intervention study (The interplay between the kinematics, dynamometric, hydrodynamics and electromyography factors) - Phornpot Chainok (2022)
Understanding the acquisition of expertise in turning skills from the perspective of a developing young swimmer generally requires the development of a relationship and interaction between characteristics of effective movement and the teaching-learning process. However, few turning biomechanical analyses on age-group swimmers have been conducted to facilitate biomechanical diagnosis and scientific intervention in backstroke to breaststroke turning techniques. The objective of this Thesis were twofold: (i) to identify the biomechanical features that have the greatest influence in each of the four different backstroke to breaststroke turning techniques and (ii) to investigate the effect of four weeks and 16 systematically contextual interference training sessions of 40 minutes each, followed by blocked, serial, and random practice on facilitating learning of the backstroke to breaststroke turning techniques. A multidisciplinary approach, including a motion capture system, a customized underwater tri-axial force plate, surface electromyography (EMG) and an inverse dynamic approach utilizing hydrodynamic variables, was used to accomplish this goal. We began (in the first study) by identifying the key biomechanical features and determinants of open, somersault, bucket, and crossover turning performance. The electromyographic (EMG) behavior and selected kinematic variables of the four backstroke to breaststroke turning techniques were compared in the second study, with a particular emphasis on rotation and push-off efficacy. The third analysis compared the hydrodynamic characteristics and pull-out strategy related to turn out efficacy. The fourth study employed the linear and tree-based machine learning models to identify the highly realistic models of backstroke to breaststroke turn performance based on comprehensive temporal, kinematic, kinetic (including hydrodynamic) variables. Finally, we looked at how a four-week intervention program that offered systematic increases in contextual interference allows age-group swimmers to improve backstroke to breaststroke turning techniques. Results pointed out that a four-week intervention program improved age-group swimmers' backstroke to breaststroke turning techniques. According to the linear and nonlinear predicted models, optimized turning performance was achieved by a compromise and continuity between the turn-in and turn-out phases. Turn-in efficacy was directly influenced by the contributions of approaching velocity to the wall and rotating abilities in improving rolling velocity and pushing-off force. The integrated electromyographic activity of eight muscles was similar across four turning techniques. The erector spinae and gastrocnemius medialis were the most activated muscles, with the crossover turn having the highest rotation and push-off iEMG values. A comparison of kinetic measures reveals that the bucket turn has a higher peak force, while a higher horizontal impulse leads to higher push-off velocity in the crossover turn. The somersault has a slightly deeper gliding depth, while hydrodynamic characteristics and pull-out strategy, as determinants of turn-out efficacy, did not differ between turning techniques.